# How do I solve for V in this equation!!?

detailed steps would be greatly appreciated!

solve for v

- 2 over 2v+4

minus 3 equals

-6 over v+2

### 2 Answers

- BillLv 79 years agoBest Answer
-2/(2v+4) - 3 = -6/(v+2)

You need to find the lowest common denominator, or LCD. Basically you want to turn all three terms into fractions that have the same denominator, then you can just add or subtract everything on top.

Your first term's denominator is 2v + 4

Your second term doesn't show a denominator, so it is 1 because 3 is the same as 3/1

Your third terms denominator is v + 2

Since both 1 & v + 2 both go into 2v + 4, 2v + 4 is the LCD. So we need to put all three terms on top of 2v + 4

Your first term is already on top of 2v + 4, so it stays at -2/(2v+4)

Your second term has 1 as it's denominator, so we need to multiply top & bottom by 2v + 4 & get 3(2v+4)/(2v+4)

Your third term has v + 2 in the denominator, so we need to multiply top & bottom by 2 & get -12/(2v+4)

Now put these back in equation form

-2/(2v+4) - 3 = -6/(v+2) is same as -2/(2v+4) - 3(2v+4)/(2v+4) =-12(2v+4)

Now if you multiply everything by 2v+4, it cancels out all 2v+4 on the bottom & you are left with

-2 -3(2v+4) = -12

-2 -6v - 8 = 12

-10 - 6v = -12

-6v = -2

v = -2/(-6) = 1/3

- 9 years ago
The problem:

-2/(2v+4) - 3 = -6/(v+2)

first you factor the denominator:

-2/2(v+2) - 3 = -6/(v+2)

then you find a common denominator for 3.

-2/2(v+2) - 3*2(v+2)/2(v+2) = -6/(v+2) simplified: -2 - 6(v+2) over 2(v+2) = -6/(v+2)

then multiply each side by v+2

-2 - 6(v+2) over 2(v+2) * (v+2) = -6/(v+2) * (v+2) simplified: -2 - 6(v+2) / 2 = -6

then multiply each side by 2

-2 - 6(v+2) = -12

add 2 to each side

-6(v+2) = -10

divide each side by -6

v+2 = -10/-6 = 5/3

subtract 2 (6/3) from each side

v = -1/3

plug it in and see if it works.